Spatial Ventilation Inhomogeneity Determined by Electrical Impedance Tomography in Patients With Chronic Obstructive Lung Disease - Frerichs, Inéz; Lasarow, Livia; Strodthoff, Claas; Vogt, Barbara; Zhao, Zhanqi; Weiler, Norbert (Frontiers in Physiology, 2021)
The aim was to examine whether electrical impedance tomography (EIT) could determine the presence of ventilation inhomogeneity in patients with chronic obstructive lung disease (COPD) from measurements carried out not only during conventional forced full expiration maneuvers but also from forced inspiration maneuvers and quiet tidal breathing and whether the inhomogeneity levels were comparable among the phases and higher than in healthy subjects. EIT data were acquired in 52 patients with COPD (11 women, 41 men, 68±11 years) and 14 healthy subjects (6 women, 8 men, 38±8 years). Regional lung function parameters of forced vital capacity (FVC), forced expiratory volume in 1s (FEV1), forced inspiratory vital capacity (FIVC), forced inspiratory volume in 1s (FIV1) and tidal volume (VT) were determined in 912 image pixels. The spatial inhomogeneity of these parameters was characterized by coefficient of variation (CV). Median CV values (interquartile ranges) in patients vs. healthy subjects were for FVC: 1.92 (1.69-2.46) vs. 1.55 (1.47-1.63), FEV1: 2.02 (1.86-2.58) vs. 1.59 (1.49-1.70), FIVC: 2.02 (1.78-2.49) vs. 1.51 (1.42-1.63), FIV1: 1.96 (1.70-2.33) vs. 1.55 (1.48-1.64), all P<0.0001, VT: 1.97 (1.72-2.25) vs. 1.64 (1.46-1.75), P=0.0001). The ventilation distribution was affected by the analyzed ventilation parameter in patients (p=0.0024) but not in healthy subjects. Receiver-operating characteristics showed that CV discriminated patients from healthy subjects with an area under the curve (AUC) of 0.835 (FVC), 0.845 (FEV1), 0.903 (FIVC) and 0.891 (FIV1), all P<0.0001. AUC for VT was 0.821 (P=0.0002). These findings confirm the ability of EIT to identify increased ventilation inhomogeneity in COPD patients.